THE EFFECT OF NOISE EXPOSURE ON THE AVERAGE NUMBER OF TEMPORAL LOBUS NEURONS IN ADULT WISTAR RATS - Suka Astini, Dewa Ayu Agung Alit; Evayanti, Luh Gde; Witari, Ni Putu Diah; Sumadewi, Komang Trisna; Prima Dewi, A.A.A Asri; Anthony Kerans, Fransiscus Fiano; Kurniawati, Ida (Universitas Udayana, 2024)
Noise is defined as unwanted and disruptive sound, considered an environmental stressor and disturbance. Noise encompasses many aspects of modern communities, including work environments. The damaging effects of noise primarily result from the unrestricted production of free radicals into the auditory organs. Exposure to noise causes various health problems, such as hearing impairment, sleep disturbances, and interference with individual performance. Reactive oxygen species (ROS), also known as free oxygen radicals, are normal by-products of cellular aerobic metabolism. These unstable molecules can damage cellular lipids, proteins, and nucleic acids in DNA if the antioxidant balance is disrupted. Acute and chronic exposure to loud noise generates excessive free radicals and disrupts extra-auditory organs such as the nervous, endocrine, and cardiovascular systems. The purpose of this study is to analyze the relationship between noise exposure and the number of neurons in the temporal lobes of Wistar rats. The research design used is a laboratory experimental design, specifically a pure experimental design, implemented with the randomized posttest-only control group design. The research sample consists of 30 male Wistar rats randomized into 2 groups, control and treatment. The treatment group is exposed to 95dB noise for 4 hours per day for 14 days. The rats are then euthanized, and their brain tissue is fixed with 10% neutral buffered formalin. Assessment is performed using Hematoxylin Eosin staining, and analysis is conducted blindly on the average number of neurons in the rat's temporal lobes. Data is subjected to normality testing using the Shapiro-Wilk test and analyzed using independent t-tests for parametric comparison. The results show a significant difference in the mean number of neurons in the temporal lobes between rats exposed to noise and the control group (p <0.005). The conclusion of this study is that noise affects neuron cells in the temporal lobes. Keywords : noise, temporal lobe, neurons.